ASSESSMENT OF STRATEGIC DIRECTIONS FOR THE IMPLEMENTATION OF PUBLIC-PRIVATE PARTNERSHIP IN THE FIELD OF SECURITY DEVELOPMENT OF THE AGRICULTURAL SECTOR - Kryshtanovych, Myroslav; Sylkin, Oleksandr (Socio-economic relations in the digital society, 2025)
The article analyzes the features of choosing the optimal strategic direction for increasing the effectiveness of public-private partnership mechanisms in the field of security development of the agricultural sector in the context of modern challenges and threats. The study covers two main strategic directions (D1 and D2), which are considered from the perspective of potential benefits, costs, opportunities and risks. The basis of the methodological toolkit is the BOCR method, which makes it possible to assess not only the benefits and costs but also the risks and prospects for the development of selected strategic solutions. In the process of applying the BOCR approach, evaluation criteria were formed for each element (B - benefits, O - opportunities, C - costs, R - risks) and pairwise comparisons were conducted, which made it possible to determine the weight of each criterion. In parallel, the consistency of expert assessments was calculated by calculating the consistency ratio, which confirmed the relevance and reliability of the results obtained. According to the results of the assessment procedures, it was established that the direction of forming a mechanism for in-depth technological cooperation and accelerating digital transformation (D2) has a higher global priority despite the higher level of risks and higher costs. This is due to the fact that the D2 strategy, in addition to expanding innovative opportunities, contributes to the creation of favourable conditions for the implementation of advanced technologies, and infrastructure development and attracting more investors to projects in the agricultural sector. In parallel, D2 meets the needs of security development in the war and post-war periods, proposing the creation of comprehensive mechanisms for cooperation and accelerating adaptation to global challenges.
Keywords: public-private partnership; agricultural sector; security development; digital transformation; BOCR method; strategic choice; risks; innovations